WAGNERIAN HEXAMETERS, HOMERIC QUESTIONS: CLASSICAL «OBSESSIONS» ON TEXT, METER AND PERFORMANCE - Mota, Marcus (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
At various stages in his career, Richard Wagner sought aesthetic solutions for his artistic projects through the reception of ideas and forms from Antiquity. Among some of his options was reworking Homeric poetry, trying to find solutions to the impasses found in the disjunction between text and performance, as he identified in the German literary tradition. In this paper, I present some moments of this search for an understanding of past rhythms in new forms of expression.